2002
DOI: 10.1021/jp014464a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Acid Sites on the Intracrystalline Diffusion of Hexanes and Their Mixtures within MFI-Zeolites

Abstract: The intracrystalline diffusivities and component loadings of mixtures of n-hexane and 2-methylpentane within silicalite-1 (crystal size 150 µm) and HZSM-5 (140 µm) have been measured at 433 K as a function of the n-hexane/2-methylpentane ratio in the gas phase (at constant total hydrocarbon pressure of 6.6 kPa) using the Positron Emission Profiling technique. Strong preferential adsorption of the linear alkane over the branched one has been observed in HZSM-5, while in silicalite only a slightly higher adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…For analogous reasons, the branched alkanes 2-methylpentane (2MP) and 3-methylpentane (3MP) cause the reduction in the self-diffusivity of the n-hexane (nC6) in nC6-2MP, and nC6-3MP mixtures. 41 Intersection blocking by branched and cyclic hydrocarbons is a plausible explanation for the observed inhibition of the cracking of n-octane using an MFI catalyst. 42 Traffic junction effects are of vital importance in modeling reactors for alkylation of benzene with ethene using the MFI zeolite catalyst (in the acidic form H-ZSM-5) to produce ethylbenzene.…”
Section: Slowing-down and Hindering Effectsmentioning
confidence: 99%
“…For analogous reasons, the branched alkanes 2-methylpentane (2MP) and 3-methylpentane (3MP) cause the reduction in the self-diffusivity of the n-hexane (nC6) in nC6-2MP, and nC6-3MP mixtures. 41 Intersection blocking by branched and cyclic hydrocarbons is a plausible explanation for the observed inhibition of the cracking of n-octane using an MFI catalyst. 42 Traffic junction effects are of vital importance in modeling reactors for alkylation of benzene with ethene using the MFI zeolite catalyst (in the acidic form H-ZSM-5) to produce ethylbenzene.…”
Section: Slowing-down and Hindering Effectsmentioning
confidence: 99%
“…The explanation is again to be found in the hindering of CH 4 diffusion due to blocking of the intersections by benzene. 74 Koriabkina et al 75 have reported experimental data for the self-diffusivities of both nC6 and 2MP in C6-2MP mixtures. Their data, which were measured at 433 K, show that both self-diffusivities are significantly reduced with increasing loading of 2MP in the mixture.…”
Section: Influence Of 1/c I On the Loading Dependence Of Diffusivitiesmentioning
confidence: 99%
“…A significant amount of work both theoretical and experimental has been carried out studying the diffusion of hydrocarbons in the MFI zeolite structure, [2][3][4][5][6][7][8][9][10][11][12][13][14][15] the framework type of industrially important ZSM-5 and its siliceous analogue silicalite. The diffusion of n-alkanes longer than octane in this framework is of considerable interest and has been studied by quasi-elastic neutron scattering (QENS) techniques in both Na-ZSM-5 16 and silicalite.…”
Section: Introductionmentioning
confidence: 99%